HANNAH ARENDT ON FREEDOM AND POLITICAL - Mans Werang (Studia Philosophica et Theologica, 2017)
Hannah Arendt is well known as a political thinker who explicates a profound meaning of political action as a public space. Politic is a space where every political concepts meet each other. For Arendt, in the modern age, people lost appreciation of political praxis and of the plurality of human affairs and the breakdown distinction between public and private.As a result, modern man does not find his freedom in politics. This paper will explore the issue of human freedom in the political public space based on the concept of Vita Activita initiated by Hannah Arrendt. Hannah Arrendt adalah salah seorang pemikir politik yang menempatkan ruang publik sebagai basis pemikirannya. Politik baginya merupakan ruang di mana segala macam gagasan politis dari masing-masing manusia maupun kelompoknya bertemu. Dalam pengamatan Hannah Arendt, ruang publik politik saat ini tidak ramah terhadap perbedaan pendapat ataupun keberagamanan. Manusia modern kesulitan untuk membedakan antara ruang publik dan ruang pribadi (private) dalam berpolitik. Akibatnya, manusia modern tidak menemukan kebebasannya dalam berpolitik. Tulisan ini akan mengupas persoalan kebebasan manusia dalam ruang publik politik berdasarkan konsep Vita Activita yang digagas oleh Hannah Arrendt